A nationwide survey on the prevalence of asbestos-related lung cancer in Japan - Mariko Niino; Taro Tomizuka; Yuka Nishina; Yuichi Ichinose; Wataru Gonoi; Takahiro Higashi (PLoS ONE, 2026)
The nationwide prevalence of asbestos-related lung cancer (ARLC) needs to be accurately estimated to adequately operate a compensation subsidy program for patients with ARLC. In the present study, we aimed to estimate the proportion of patients with ARLC among patients with primary lung cancer according to the criteria established in the Japanese national compensation system, and described the characteristics and distribution of ARLC,. All facilities that treated patients diagnosed with lung cancer in 2016 were requested to submit computed tomography (CT) images of ten patients who were randomly selected from the national databases of hospital-based cancer registries. ARLC was defined as pleural plaques (PPs) extending over one-quarter of the inner lateral chest wall or existing PPs accompanied by obvious lung fibrosis. We estimated the proportion and distribution of ARLC among primary lung cancer cases and compared the characteristics of ARLC with those of primary lung cancer. Of the 772 facilities that treated at least one patient with lung cancer, 370 facilities provided 3,565 sets of CT images. Among them, 216 (6.1%) patients had PPs, and 86 (2.4%) patients met the compensation criteria. After sample weighting, 2.0% of all primary lung cancers were classified as ARLC in Japan. Compared with other primary lung cancers, a higher percentage of patients with ARLC were male (94.2% vs. 68.6%; P < 0.01) and had more advanced-stage disease (stage III: 22.1% vs. 16.0%; stage IV: 44.2% vs. 39.8%; P = 0.05). Most patients with ARLC (53.5%) were diagnosed at designated cancer hospitals. The proportion of patients with squamous cell carcinoma was higher in patients with ARLC than in those with primary lung cancer (25.6% vs. 18.6%; P < 0.01). The estimated number of patients with ARLC was higher than expected from the number of applicants in the Asbestos Health Damage Relief System for asbestos-related health damages. Thus, countermeasures are needed to accurately identify eligible compensation recipients.